2000
DOI: 10.4049/jimmunol.165.12.7140
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Expression Cloning of aMycobacterium tuberculosisGene Encoding a Protective Antigen Associated with the Early Control of Infection

Abstract: Infection of C57BL/6 mice with Mycobacterium tuberculosis results in the development of a progressive disease during the first 2 wk after challenge. Thereafter, the disease is controlled by the emergence of protective T cells. We have used this infection model in conjunction with direct T cell expression cloning to identify Ags involved with the early control of the disease. A protective M. tuberculosis-specific CD4 T cell line derived from mice at 3 wk postchallenge was used to directly screen an M. tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 51 publications
1
95
0
Order By: Relevance
“…34,35 Many attempts have been made to elucidate the natures of the TB antigens involved in stimulating protective IFN-g production. Actually, it was reported that IFN-g production specific for antigens of M. tuberculosis such as Ag85A, 35,36 Ag85B, 35,37 MTB41, 38 and ESAT-6 39 dramatically reduces in patients with active TB but not in HTR, suggesting that these antigens may be candidate protective antigens. 8 In the case of Ag85A, it was also demonstrated that the reduced production of IFN-g in response to Ag85A was significantly restored in PBMCs 35 after anti-TB chemotherapy in patients with active disease, suggesting that Ag85A-specific IFN-g response might be involved in the clinical phenotype and immunopathogenesis of human active pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Many attempts have been made to elucidate the natures of the TB antigens involved in stimulating protective IFN-g production. Actually, it was reported that IFN-g production specific for antigens of M. tuberculosis such as Ag85A, 35,36 Ag85B, 35,37 MTB41, 38 and ESAT-6 39 dramatically reduces in patients with active TB but not in HTR, suggesting that these antigens may be candidate protective antigens. 8 In the case of Ag85A, it was also demonstrated that the reduced production of IFN-g in response to Ag85A was significantly restored in PBMCs 35 after anti-TB chemotherapy in patients with active disease, suggesting that Ag85A-specific IFN-g response might be involved in the clinical phenotype and immunopathogenesis of human active pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…mAbs were generated from hybridoma supernatants from the anti-panHLA (W6/32), anti-HLA-B,C (B1. 23 (24,25), 38 kDa (26), and ESAT-6 (27) proteins were prepared as previously described (18).…”
Section: Monoclonal Abs and Reagentsmentioning
confidence: 99%
“…In fact, the PE and PPE genes are ten times more frequent among the 100 most volatile M. tuberculosis genes than they are in the genome as a whole. The elevated volatility of these genes indicates increased pressure for amino-acid substitutions, presumably because of diversifying selection mediated by interactions with the host immune system 12,13 . These results, based on a single genome sequence, agree with an extensive study in which the authors compared the genomes of two fully sequenced M. tuberculosis strains 2 .…”
mentioning
confidence: 99%
“…2). For both pathogens, the genes with extreme volatility are distributed throughout the genome.The PE and PPE gene families of M. tuberculosis, which are putatively expressed on the extracellular surface and exhibit extensive non-synonymous variability 2 , have been identified as potential antigens for the host immune response [11][12][13] . The PE family (81 genes) and the PPE family (57 genes) both exhibit significantly greater volatility than the other genes in the M. tuberculosis genome (P w ¼ 6 £ 10 28 for PE and P w ¼ 3 £ 10 222 for PPE; Wilcoxon Figure 1 Two examples of calculating codon volatility.…”
mentioning
confidence: 99%